Investor heterogeneity, trading account types and competing liquidity channels for Malaysian stocks - Lim, K.P.; Thian, T.C.; Hooy, C.W. (Elsevier, 2017)
This paper examines the relationship between various investor groups and stock liquidity for Malaysian public listed firms over the 2002–2009 sample period. Using the Amihud illiquidity ratio, we extend the literature by addressing the issues of investor heterogeneity, trading account types and the interactions of competing liquidity channels. The analysis reveals that only local institutions and local individual investors who trade through the direct accounts are significantly associated with the liquidity of domestic firms. In contrast, the significant liquidity effect for foreign investors operates through the nominee accounts. While institutional ownership exhibits a linear negative relationship, our findings on local individuals and foreign nominees differ greatly from previous studies in that their relationship with stock liquidity is non-monotonic. Apart from the widely-researched information asymmetry and trading effects, we find that liquidity is also driven by the largely ignored information competition channel. An important insight from our findings is that the large shareholdings by any particular investor group is detrimental to stock liquidity as they exacerbate information asymmetry, reduce the degree of competition and lower the level of trading activity.